Pengembangan Material Bioplastik Ramah Lingkungan Berbahan Dasar Limbah Pertanian - Asti Raisha (Jurnal Sains dan Teknologi Indonesia, 2025)
This study aims to explore the potential of agricultural waste as a primary raw material for developing eco-friendly bioplastic materials. The extensive use of petroleum-based plastics has caused serious environmental problems due to their non-biodegradable nature, thus requiring more sustainable alternatives. Agricultural residues such as rice straw, sugarcane bagasse, cassava peels, pineapple leaf fibers, and rice husks were selected for their abundance and high lignocellulose content. The research methodology includes starch or cellulose extraction from the residues, bioplastic formulation with natural plasticizers, and testing of physical, mechanical, and biodegradability properties. The results show that bioplastics derived from agricultural waste exhibit competitive mechanical strength, adequate water resistance, and faster biodegradation rates compared to conventional plastics. The addition of nanosilica filler from rice husk ash significantly improved flexibility and tensile strength of the bioplastic. These findings highlight that agricultural waste-based bioplastics can serve as an innovative solution to reduce plastic pollution while supporting circular economy principles. Therefore, the development of bioplastics from agricultural residues not only provides environmental benefits but also creates economic opportunities for rural communities and local resource-based industries.